Botulinum Toxin-A Therapy in Pediatric Urology: Indications for the Neurogenic and Non-Neurogenic Neurogenic Bladder - Lori Dyer; Israel Franco (The Scientific World Journal)
Although, the role of Botulinum Toxin-A in the treatment of the neurogenic and non-neurogenic neurogenic bladder is becoming more defined, this is the first review article to characterize the emerging role of Botulinum Toxin-A in the pediatric urologic population. Injection of Botulinum Toxin-A at the level of the bladder works by inhibiting uninhibited bladder contractions and, possibly, by blocking some of the sensory nerve fibers. In children with sphincter dyssynergy, injection at the level of the urethral sphincter works by inhibiting the involuntary guarding reflex and blocking dyssynergic voiding.